A comparative study on the loan products "Life Line" : Dutch Bangla Bank Limited - Rahman, Qazi Mashiur (BRAC university, 2011)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2009.